E-LEARNING ENGLISH AS A FOREIGN LANGUAGE (EFL) BY MEANS OF USING THE JOURNALISTIC STYLE - Díaz-Luis, Natacha Rita (PEOPLE: International Journal of Social Sciences, 2021)
The journalistic style is a sociocultural phenomenon becoming more common in our reality because of the continuous exposition of media in citizens’ experience. This exposition formulates our conception, reinterpretation and construction of the world, as well as it allows us to get to know a great diversity of perspectives among one single concept. Throughout the following journalistic article, the journalistic style has been reconstructed to make students understand and learn new methods of communication regarding the linguistic and communicative norms that media possesses. Moreover, students will be able to learn the different essential features that compose the process of newspaper creation: journalistic article structuration, journalistic cohesion, advertisement production, sections that compose the journalistic piece, etc. Indeed, the aim was to teach and study the digitalization of the English language in a journalist style, thus, using the language in new formats and linguistic contexts. For this study, a group of students belonging to the second year of Secondary Education has been selected. The learning situation was initially based on the comprehension and interpretation of the journalist production of newspapers’ productions and eventually, a newspaper was created. Two major skills were developed during the learning of English as a foreign language: reading comprehension and written production. The results obtained were positive: Pupils demonstrated digital structures learning, assimilation of uses of English regarding descriptive and persuasive uses and knowledge about areas and structuration of newspapers.